1984
DOI: 10.1093/bja/56.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age on Spinal Anaesthesia With Isobaric 0.5° Bupivacaine

Abstract: Possible correlations between age and certain characteristics of spinal blockade with plain bupivacaine were investigated in 124 patients, ages ranging from 15 to 92 yr. Three millilitre of 0.5% solution (sp. gr. 1.000 at 37 degrees C) was injected at the L3-L4 interspace. There were great individual variations in all age groups, but the maximum spread of analgesia increased with age, although the correlation was poor (P less than 0.05). The spread of analgesia to L2 and L3 segments in the oldest patients (gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 0 publications
3
44
1
2
Order By: Relevance
“…However, the difference, even when statistically significant, concerned only 3 dermatomes between 20 and 80 years, which limits the findings' true clinical relevance. 27 Further studies are indicated to better understand any such relationship.…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference, even when statistically significant, concerned only 3 dermatomes between 20 and 80 years, which limits the findings' true clinical relevance. 27 Further studies are indicated to better understand any such relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the unpredictability of the spread of spinal anesthesia [1], patient-dependent factors, for example body mass index (BMI) [2][3][4], weight, height [2], age [5], and volume of cerebrospinal fluid [6,7], have been pointed out as determinants of the sensory block level in surgical patients. Leino et al [8] have recently observed a greater spread of spinal block, and a greater effect of BMI on the spread of spinal block in rheumatoid patients compared with non-rheumatoid control patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…Isobaric bupivacaine has shown variable spread in different age groups 12,13 . A correlation between sensory block level and age was observed in patients aging from 15 to 92 years treated with 3 ml 14 , and in patients aging from 33 to 97 years 15 treated with 4 ml of 0.5% isobaric bupivacaine. There are no reports in the literature about the cephalad spread of analgesia with 2% isobaric lidocaine as a function of patients' age.…”
Section: Introductionmentioning
confidence: 84%